2016
DOI: 10.1158/1078-0432.ccr-15-1125
|View full text |Cite|
|
Sign up to set email alerts
|

RAS/MAPK Activation Is Associated with Reduced Tumor-Infiltrating Lymphocytes in Triple-Negative Breast Cancer: Therapeutic Cooperation Between MEK and PD-1/PD-L1 Immune Checkpoint Inhibitors

Abstract: Purpose Tumor-infiltrating lymphocytes (TILs) in the residual disease (RD) of triple-negative breast cancers (TNBCs) after neoadjuvant chemotherapy (NAC) are associated with improved survival, but insight into tumor cell-autonomous molecular pathways affecting these features are lacking. Experimental Design We analyzed TILs in the RD of clinically and molecularly characterized TNBCs after NAC and explored therapeutic strategies targeting combinations of MEK inhibitors with PD-1/PD-L1-targeted immunotherapy i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
377
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(399 citation statements)
references
References 42 publications
20
377
2
Order By: Relevance
“…Monoclonal antibodies trigger antibodydependent cellular cytotoxicity that subsequently activates antigen-presenting cells, a phenomenon observed with trastuzumab in HER2-positive breast cancers [70]. Certain oncogenic drivers, such as the Ras/MAPK pathway, may specifically downregulate MHC proteins and TILs, implying that inhibition may synergize with checkpoint inhibition [49]. A variety of other approaches to augment T-cell infiltration, including standard or personalized/neoantigen vaccines, chemotherapy or radiotherapy, immune agonists targeting a variety of molecules including STING, adoptive T-cell transfer, and others are under investigation.…”
Section: Common Strategies To Enhance Tumor Immunogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal antibodies trigger antibodydependent cellular cytotoxicity that subsequently activates antigen-presenting cells, a phenomenon observed with trastuzumab in HER2-positive breast cancers [70]. Certain oncogenic drivers, such as the Ras/MAPK pathway, may specifically downregulate MHC proteins and TILs, implying that inhibition may synergize with checkpoint inhibition [49]. A variety of other approaches to augment T-cell infiltration, including standard or personalized/neoantigen vaccines, chemotherapy or radiotherapy, immune agonists targeting a variety of molecules including STING, adoptive T-cell transfer, and others are under investigation.…”
Section: Common Strategies To Enhance Tumor Immunogenicitymentioning
confidence: 99%
“…Tumor infiltrating lymphocytes (TILs) in pretreatment tumor samples are associated with improved response to neoadjuvant chemotherapy in TNBC and survival among those patients with residual disease after neoadjuvant chemotherapy [46][47][48][49]. Lymphocytes can intercalate between tumor cells (intratumoral TILs) or infiltrate the surrounding stromal tissue (stromal TILs).…”
Section: Host Anti-tumor Immunity In Tnbcmentioning
confidence: 99%
“…Loi et al (from Peter MacCallum Cancer Centre, Melbourne, Australia) documented that increased tumor infiltration by T cells is associated with improved prognosis in patients affected by triple-negative breast cancer (TNBC) with residual disease following neoadjuvant chemotherapy (consisting of doxorubicin, cyclophosphamide, and in some cases paclitaxel). 238 Cornelissen and collaborators (from Erasmus MC Cancer Institute, Rotterdam, Netherlands) reported that combining DC-based vaccines with metronomic cyclophosphamide (which efficiently reduces circulating T REG cells) resulted in radiographic tumor control (and increased overall survival) in 8 out of 10 patients with malignant pleural mesothelioma patients. 239 Schijns and colleagues (from Wageningen University, Wageningen, Netherlands) found that individuals with recurrent glioblastoma multiforme (GBM) receiving a vaccine composed of autologous antigens in combination with cyclophosphamide, experienced improved overall survival.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…118 Importantly, several additional preclinical data confirmed that double blockade of MAPK inhibitors and the PD-1/PD-L1 pathway mounted a synergistic antitumor function. [119][120][121][122] In Kirsten rat sarcoma viral oncogene-mutant NSCLC, investigators pointed out that the MAPK signaling pathway and downstream transcription factor, activator protein-1 are crucial for PD-L1 expression. 123 The MAPK inhibitor might somehow dampen the efficacy of PD-1/PD-L1 inhibitors.…”
Section: Combined With Targeted Therapymentioning
confidence: 99%